Modelling the performance of aero-gas turbine engine using algae-based biofuel with emission prediction - Azami, Muhammad Hanafi; Mustafa, Muhamad Zaki; Savill, Mark; Li, Yi-Guang (IOP Publishing Ltd, 2019)
The world oil consumption is at the peak where the fuel price is insubstantial and can increase dramatically due to economic, social, and political factors and unprecedented stability. Since fuel resources are scarce, it is an urgent need to find alternative fuel. Biofuel is one of the favorable choices in the market. Algae-based biofuel is the fourth generation of biofuel where it does not compete with the food production and it has myriad of advantages. These abundant algae are easy to cultivate and researchers found that algae-based biofuel is capable of reducing engine emission. This paper modelled the RB211 aero-gas turbine engine by utilizing algae-based biofuel with various blended percentage ratios at different flight conditions. Cranfield's University in-house software, PYTHIA, and HEPHAESTUS are used to model the engine performance and emission prediction respectively. PYTHIA programme uses a modified Newton-Raphson convergence technique in the zero-dimensional steady-state model for both design and off-design conditions. Meanwhile, HEPHAESTUS software uses the Zeldovich equations (for NOx) and models the emission by implementing a partially-stirred reactor (PSR) model and perfectly stirred reactor (PSRS) models at different zones in the combustor. Results have shown that thrust force produced is increasing at higher blended percentage ratio of algae biofuel. Through emission analysis prediction, generally, the nitrous oxide emission formation is lower at a higher altitude during the cruising. Results also predicted that higher percentage blended ratio of algae biofuel also reduces the emission formation.